2022
DOI: 10.1038/s41523-022-00434-w
|View full text |Cite
|
Sign up to set email alerts
|

HER2-low-positive breast cancer: evolution from primary tumor to residual disease after neoadjuvant treatment

Abstract: Approximately a half of breast tumors classified as HER2-negative exhibit HER2-low-positive expression. We recently described a high instability of HER2-low-positive expression from primary breast cancer (BC) to relapse. Previous studies reporting discordance in HER2 status between baseline biopsy and residual disease (RD) in patients undergoing neoadjuvant treatment did not include the HER2-low-positive category. The aim of this study is to track the evolution of HER2-low-positive expression from primary BC t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
42
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(45 citation statements)
references
References 45 publications
2
42
0
1
Order By: Relevance
“…Federica Miglietta et al. performed a retrospective study of 488 cases and obtained a consistent result that a lower proportion of pCR in HER2-low breast cancer patients (21.4%) after NACT than HER2-negative ones (33.6%) ( 27 ). Furthermore, another study including four prospective neoadjuvant clinical trials have reported analogous findings (pCR rates: 29.2% (HER2-low) vs 39.0% (HER2-negative)), which also showed that the proportion of pCR was significantly lower in HER2-low tumors versus HER2-negative tumors in the ER-positive subgroup ( P = 0.024) but not in the ER-negative subgroup ( P = 0.21).…”
Section: Discussionmentioning
confidence: 88%
“…Federica Miglietta et al. performed a retrospective study of 488 cases and obtained a consistent result that a lower proportion of pCR in HER2-low breast cancer patients (21.4%) after NACT than HER2-negative ones (33.6%) ( 27 ). Furthermore, another study including four prospective neoadjuvant clinical trials have reported analogous findings (pCR rates: 29.2% (HER2-low) vs 39.0% (HER2-negative)), which also showed that the proportion of pCR was significantly lower in HER2-low tumors versus HER2-negative tumors in the ER-positive subgroup ( P = 0.024) but not in the ER-negative subgroup ( P = 0.21).…”
Section: Discussionmentioning
confidence: 88%
“…ADC drugs improve survival not only in HER2-positive breast cancer patients, but also in patients with low expression of HER2. HER2-low-expressing breast cancer is a heterogeneous group of HER2-low-expressing population ( 20 , 21 ). The results of the DESTINY-Breast04 study showed that compared to the physician-selected treatment group, patients on trastuzumab deruxtecan with low expression of HER2 showed unprecedented statistically significant and clinically meaningful improvements in PFS and OS.…”
Section: Discussionmentioning
confidence: 99%
“…Discrepancies are also found in the influence of the HER2-low status on the pathological complete response (pCR) rate of patients receiving neoadjuvant chemotherapy (NACT) [12,13,15]. The diverse evolution of HER2 status before and after NACT have been observed in previous studies [16][17][18]. These controversial results suggest that the clinicopathological characteristics and prognostic value of HER2-low patients with early BC receiving NACT warrant further research.…”
Section: Introductionmentioning
confidence: 99%